A Nucleotide Signature for the Identification of American Ginseng and Its Products - Liu, Yang; Wang, Xiaoyue; Wang, Lili; Chen, Xiaochen; Pang, Xiaohui; Han, Jianping (Frontiers in Plant Science, 2016)
American ginseng (derived from Panax quinquefolius) is one of the most widely used medicinal herbs in the world. Because of its high price and increasing demand, there are many adulterants on the market. The proposed internal transcribed spacer 2 (ITS2) has been used to identify raw medicinal materials, but it is not suitable for the identification of Chinese patent medicine ingredients. Therefore, a short barcode for the identification of processed American ginseng and its corresponding Chinese patent medicines would be profitable. In this study, 94 samples of American ginseng and Asian ginseng were collected from all over the world. The internal transcribed spacer 2 (ITS2) region was sequenced, and a nucleotide signature was developed based on one single nucleotide polymorphism (SNP) site unique to American ginseng. The nucleotide signature (atcactcctt tgcgggagtc gaggcgg) consists of 27 bases over the length of the ITS2 sequence (420 bp). Furthermore, we also designed primer pairs to amplify the nucleotide signature; the specific primer pair 4F/4R has been found to be unique to the ginseng species and capable of amplifying the nucleotide signatures from Chinese patent medicines and decoctions. We used the nucleotide signature method to inspect ginseng products in Chinese patent medicines; 24 batches of Chinese patent medicine from stores in Beijing were amplified and sequenced successfully. Using the double peaks at the SNP sites of the nucleotide signature, 5 batches were found to be counterfeits, and 2 batches were found to contain adulterants. Thus, this nucleotide signature, with only 27 bp, has broadened the application of DNA barcoding in identification of decoctions, Chinese patent medicines and other ginseng products with degraded DNA. This method can rapidly identify ginseng products and could also be developed as an on-site detection method.